The Effect of Good Corporate Governance, Capital Structure on Financial Performance with Profit Management as Mediation: Case Study in the Health Industry - Ratna Indrawati; Fikri Hanif (Global Writing Academica Researching and Publishing, 2023)
The importance of the health industry in Indonesia as the leader in public health care can be observed in the pandemic scenario, where this sector is at the forefront of pioneering. With the use of profits management, this research attempts to assess the variables affecting the performance of healthcare firms listed on stock exchanges for the years 2018 through 2021. 24 health firms that were listed on the Indonesian stock market between 2018 and 2021 made up the sample for this research. Panel data regression and time series analysis are used to analyze the data. The findings of this research suggest that neither the capital structure nor GCG have any impact on the company's ability to control its profitability. The company's capital structure has an impact on its financial performance; GCG has no such impact. While the company's financial success is impacted by earnings management. It is also anticipated that additional research will include financial ratio variables, such as liquidity ratios like the current ratio, quick ratio, and cash ratio to assess the liquidity of the healthcare sector, in addition to activity ratios like receivables, inventory turnover, and asset turnover, to improve the accuracy of the research findings. In order for investors to utilize the data to make investment choices, health firms need to analyze associated earnings management and financial performance.